Blessing or curse?: Domestic plants' survival and employment prospects after foreign acquisitions - Sourafel Girma; Holger Görg (Institute for the Study of Labor (IZA), 2003)
This paper investigates whether the acquisition of a domestic establishment by a foreign owner has any effects on the survival prospects and employment growth of that plant. The analysis uses plant level data for the UK electronics and food industries for the period 1980 to 1993. We control for possible endogeneity using a matched sample of firms and instrumental variables. Estimating a standard hazard model yields the result that foreign takeover reduces the liftetime of the acquired plant in both the electronics and food sectors. Estimations of the determinants of employment growth in domestic plants provide some evidence that the incidence of takeover reduces employment growth, in particular for unskilled labour in the electronics industry. There is no significant effect for the food sector, however.
Keywords: 330; acquisitions; survival; employment growth; foreign direct investment; Direktinvestition; Elektronikindustrie; Beschäftigungseffekt; Großbritannien